Does Brexit mean the end for Critical Management Studies in Britain?. (September 2018) - Grey, Christopher
My argument in the Speaking Out essay is, first, that in the European Union Referendum vote, Critical Management Studies found itself on the same, anti-Brexit, side as big business and mainstream management studies, making it hard to sustain itself as something separate from these. Second, I argue that this reflects a wider set of issues about the liberal-left and the European Union, which, third, means that British Critical Management Studies now finds itself located within what is regarded on the pro-Brexit side as 'the establishment elite', and that to work effectively against Brexit, British Critical Management Studies will need to work as part of that establishment elite. My conclusion is that this may mark the end of British Critical Management Studies as it has hitherto existed.